Development of a bioactive dentin adhesive resin modified with magnesium-doped synthetic hydroxyapatite crystals. (April 2023) - Daood, Umer; Fawzy, Amr
Abstract: The aim is to evaluate the development of an experimental multi-mode/Universal resin-based dentin adhesive modified with synthetic Mg 2+ doped hydroxyapatite crystals (HAp) having self-remineralization and antibiofilm properties. HAp doped with Mg 2+ was prepared by the precipitation method. Experimental adhesives were subjected to degree of conversion and X-ray diffraction test for size and crystal structure. Bond strength was tested, and electron microscopy (SEM/TEM) imaging of resin-dentin interface was done along with nanoleakage, nanoindentation, confocal and Raman analyses. S. mutans was analysed using CLSM images against modified adhesive specimens. Nucleating abilities within the resin-dentin specimens are determined by measuring Ca 2+ . Alkaline phosphatase, Runx2, and Ocn transcripts are amplified using quantitative polymerase chain reaction (q-PCR). A calcium assay is performed to quantify level of mineralisation. When compared to control adhesives, the 0.5% Hap/Mg 2+ containing experimental dentin adhesive demonstrated improved interaction with dentin. The preservation of uniform intact hybrid layer with the absence of nanoleakage indicated dentin bond integrity with 0.5% HAP/Mg 2+ modified adhesive. Self-remineralization and antibiofilm potentials are supported. Graphical abstract: Image 1 Highlights: Bioactive Dentin Adhesive with Synthetic Hydroxyapatite Crystals and Magnesium. Self-remineralsation and antibiofilm. First report of HAp with Mg crystals. Continuous releasing ions. Prevention of caries. Preservation of organic structure of the inner dentin structure.